Website detection for phishing attack by using browser extension - Putera Nuriqmar Iskandar, Ahmad Basri (2018)
Internet is a worldwide framework that can be utilized for sharing data, giving overall administrations and correspondence. However there are problem in term of security. In this thesis we focus on phishing attack. Phishing is a criminal trap of taking unfortunate casualties individual data by sending them spoofed email encouraging them to visit a produced site page that resembles a genuine one of an authentic organization and requests that the beneficiaries enter individual data, for example, Mastercard number, secret word and so forth. The current problem that occur are implanting a connection in an email that diverts to an unbound site that demands delicate data. Satirizing the sender deliver in an email to show up as a respectable source and demand delicate data. The main objective of this research is to investigate phishing attack are to investigate current method on phishing attack, to propose the arrangement exposure assault dependent against the browser extension alert, to evaluate the suggested arrangement inspection assault dependent on the website browser. The methodology that been use in this research is first planning, second phase analysis, third phase implementation, fourth phase conclusion and last phase is documentation. The result of this research show that rule base approach manage to detect the phishing website which are also connected to phishitank database. There are 3 rule that been use in this research out of 14 rule. After running the extension, "Developer mode" must be activated first since this made extension is an unloaded extension and furthermore not enlisted yet in Google Chrome. From this examination, it is clear that the built framework is actualized by utilizing extension in Google Chrome. In Conclusion, the goal of this thesis has been achieved by testing the framework in the Google Chrome internet browser